K.S. Maniam’s Bestiary: Reading Animality and Identity in Selected Stories - Yeow, Agnes S. K. (SARE: Southeast Asian Review of English, 2021)
This essay scrutinises K. S. Maniam’s fictional animals by going beyond the confines of metaphor to interrogate the concept of animality and how animality impinges on diasporic identity. I examine the writer’s impulse to animalise the notion of national belonging especially though the strategic deployment of the animal mask. I argue that Maniam’s critique of animality suggests that migrant and animal lives are interlinked and informs his re-envisioning of the diasporic self.